Representasi Hegemoni pada Film “Miracel in Cell No. 7” Karya Hanung Bramatyo - Husen, Mohammad Husen; Mohammad Saied; Nur Rizqiyanti; Ahmad Ilzamul Hikam (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
. Film as a mass communication medium not only functions as entertainment, but also as a means of representing power relations in society. Miracle in Cell No. 7 works by Hanung Bramantyo show various forms of official domination and legal inequality which are relevant to be studied through a hegemony perspective. This research aims to describe the forms of hegemony that appear in the film and interpret the social criticism conveyed through the narrative and visualization. The research uses qualitative methods with listening and note-taking techniques, then the data is analyzed through reduction, presentation and drawing conclusions based on Antonio Gramsci's theory of hegemony. The research results show that this film contains four forms of hegemony: ideological hegemony through the instillation of disciplinary values; hegemony of power through apparatus domination and abuse of authority; cultural hegemony through the imposition of a single standard of behavior; and moral hegemony through the formation of ethical judgments that benefit those in power. These findings indicate that films not only present emotional stories, but also present criticism of legal injustice and structural domination. This research confirms that visual media plays an important role in forming public awareness regarding the practice of power in social life.